Attitudes toward Community - based training and internship of Nursing students and professors: a qualitative study - Zhila Fereidouni; Mahmood Hatami; Ali Khani Jeihooni; Hannan Kashfi (Universidad de Antioquia, 2017)
Objective. To explore the attitudes of nursing students and professors towards community-based training and internship in Fasa, Fars, Iran. Methods. This qualitative study was conducted using the content analysis approach. Data from students and professors were collected through five focal groups and data from patients was collected by using field notes. Interviews were conducted with 17 students and three professors responsible for implementing the study plan; in addition, 800 patient-related field notes were analyzed. Results. Community-based training and internship were identified as useful from the point of view of students, professors, and clients. Results were classified into two principal categories: "health preservation and promotion" and "promotion of students' skills". Conclusion.  Attitudes toward the formation and community internship are favorable insofar as it is a highly beneficial experience for students, professors, and patients.   How to cite this article. Fereidouni Z, Hatami M, Jeihooni A, Kashfi H. Attitudes toward Community - based training and internship of Nursing students and professors: a qualitative study. Invest. Educ. Enferm. 2017; 35(2):243-251.